(untitled) (Eurasian Journal of Religious Studies, 2018)
Islamic law is one of the independent legal systems. At the current stage, research conducted in this branch of law is relevant and forward-looking. In the Muslim world, the methodology of theological schools (mazhabs) is maintained, which are the guarantor of the preservation of Islam as a whole and the development of new methodologies in accordance with historical, national, cultural and other conditions. The relationship of Islam with the heritage of the ancient world is phenomenal. The interest in culture and science, as well as their success during blossoming of the Islamic Empire are of great importance in the history of Muslim civilization. Exploring this phenomenon, we understand that Muslim culture is not essentially Arabic or Indian, Turkic or Iranian, but this unique form of Islamic civilization that represented by a combination of heritage of ancient traditions and the source of the development of a particular Islamic civilization contributing to the spread of Islam in general. An analysis of the application of Islamic law helps to develop an assessment method by which one can more deeply study the essence and significance of the religious legal system in Islam as a whole. The impact of globalization on Islamic law sets tasks that require more detailed study to bring new rules in line with new conditions. The article discusses the sources of Islamic law, as well as the contribution of scholars of the Hanafi school, their works and research.